DETERMINATION OF THE RELIABILITY OF THE GAS GENERATOR OF THE STORAGE SYSTEM AND HYDROGEN SUPPLY - Abramov, Y.; Kryvtsova, V.; Mikhailyuk, А. (Municipal economy of cities. Series: «Economy science», 2023)
It is noted that as a generalized characteristic of the functional gas generator, which is sensitive to variations in its parameters, it is advisable to use the transfer function, or its analogue - the amplitude-phase frequency characteristic of the gas generator. The amplitude-phase frequency characteristic of the gas generator includes two components - amplitude-frequency and phase-frequency characteristics. During the operation of the gas generator, there will be variations in its parameters - transmission coefficient and time constants, due to aging processes and the influence of external factors. Variations in the parameters of the gas generator lead to variations in its amplitude-frequency and phase-frequency characteristics. Mathematical models for variations in the frequency characteristics of the gas generator are built and it is shown that their frequency range should be limited by the bandwidth of the gas generator. The upper limit of the bandwidth of the gas generator is determined by the root of the biquadratic algebraic equation. For the typical parameters of the gas generator using a hydroreactive sample based on sodium aluminate, graphical dependences of variations of its amplitude-frequency and phase-frequency characteristics are constructed depending on variations of the transmission coefficient, time constants, and frequency. These dependencies are used to determine the parameters of the normal distribution law of variations in the frequency characteristics of the gas generator. In accordance with Lyapunov's rule, a normative law for the distribution of variations in the frequency characteristics of the gas generator is adopted. Due to the symmetry of the distribution of variations in the amplitude-frequency and phase-frequency characteristics of the gas generator, their mathematical expectations are equal to zero. Obtaining estimates of the amplitude and phase reliability of the gas generator is carried out using the Laplace function. The argument of this function is the permissible values of the frequency characteristics of the gas generator and their root mean square deviations. It is shown that with probabilities of 0,9973 and 0,9812, the amplitude-frequency and phase-frequency characteristics of the gas generator will not differ more than when it is turned on.